Molecular diversity of water mites of the Turkish eastern Black Sea basin, with the description of two new species (Acari, Hydrachnidia) - Pešić, Vladimir; Bayçelebi, Esra; Zawal, Andrzej; Bańkowska, Aleksandra; Jovanović, Milica; Kumru, Salih; Baytaşoğlu, Hazel; Kalayci, Gökhan (Zootaxa, 2026)
This study identified water mites collected from coastal streams in the provinces of Rize and Trabzon, which flow directly into the Black Sea, using both molecular and morphological approaches. A total of 42 COI barcodes were generated and clustered into 19 BINs, corresponding morphologically to 15 species. Two species, Hygrobates turani sp. nov. and Atractides karadenizensis sp. nov. (Hygrobatidae), are described as new to science, while Sperchon milisai Pešić, 2022, and Hygrobates grabowskii Pešić, Saboori, Zawal & Dabert, 2019, are newly reported from Türkiye. The study demonstrates that only a small fraction of Türkiye’s water mite diversity can currently be identified using existing DNA-barcode libraries, highlighting the need for their further expansion and refinement in future research.